2007
DOI: 10.1007/bf03403712
|View full text |Cite
|
Sign up to set email alerts
|

Splashpads, Swings, and Shade

Abstract: Background: Physical activity is a modifiable behaviour that can help curtail the increasing worldwide problem of childhood obesity. Appropriate recreational opportunities, including neighbourhood parks, are particularly important for promoting physical activity among children. Because children's use of parks is mainly under the influence of their parents, understanding parents' preferences is essential for creating the most inviting and usable park space to facilitate children's physical activity. Methods: Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 39 publications
2
10
0
2
Order By: Relevance
“…At a community level, researchers have begun to highlight the physical environment in city and area planning as one approach to combat rising obesity and diabetes rates. Research on obesogenic environments (environments that encourage physical inactivity and poor eating habits), high-risk generations of children, and parent’s preferences for parks in the city of London stress the importance of neighbourhoods for one’s physical, social and mental well-being, and incorporating both the natural and built environment in city and area planning [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a community level, researchers have begun to highlight the physical environment in city and area planning as one approach to combat rising obesity and diabetes rates. Research on obesogenic environments (environments that encourage physical inactivity and poor eating habits), high-risk generations of children, and parent’s preferences for parks in the city of London stress the importance of neighbourhoods for one’s physical, social and mental well-being, and incorporating both the natural and built environment in city and area planning [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this null finding supports the idea that average distance to parks/green space may not be an important feature of the built environment in communities like Calgary that are characterized by high car use. A recent Canadian study showed that, while 49% of parents reported frequenting the park closest to their home, the majority of respondents reported travelling more than 4 km to get to their desired park[ 60 ]. For those parents who chose to travel to a park, park location was not as important as park amenities[ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of trees and natural features are common neighborhood characteristics that represent the quality of greenness and have been linked with PA behavior [16,17,31,32,33]. Shade is another facet of the quality of the natural environment but has mostly been studied within the parks and educational settings [34,35,36,37,38,39]. However, shade should be included in studies of nearby nature and PA, given that outdoor-based PA may carry some risks due to extreme heat, thermal discomfort [40], and harmful levels of UV exposure from the sun.…”
Section: Introductionmentioning
confidence: 99%